Chapter Plant Name Resources Building Bridges with Users - Paton, Alan (United Nations Educational, Scientific and Cultural Organisation (UNESCO), 2016)
Plant names are the key to communicating and managing information about plants. This paper considers how providers of high quality technical plant name information can better meet the requirements non-botanical audiences who also rely on plant names for elements of their work. The International Plant Name Index, World Checklist of Selected Plant Families and The Plant List are used as examples to illustrate the strengths and weaknesses of plant name resources from a non-expert user's perspective. The above resources can be thought of as botanists pushing data at audiences. Without closer engagement with users, however, there is a limit to their relevance and impact. The need to cover common names is a frequent criticism of existing resources. The Medicinal Plant Names Services (MPNS, www.kew.org/mpns) is an example of how plant name resources can be adapted to better address the needs of a non-botanical audience. Some of the major challenges are outlined and solutions suggested.